Effect of Compensation, Quality of Work Life on Performance - Komar, Irsan; Brahmasari, Ida Aju; Nugroho, Riyadi (Journal of Asian Multicultural Research for Economy and Management Study, 2021)
This study aims to determine the effect of compensation, quality of work life on employee performance at the Directorate General of Customs and Excise, East Java Regional Office I. The study population was 1323 employees. employees, the number of samples is 200 respondents. The technique of collecting data through a questionnaire. Model testing with structural equation modeling (SEM) analysis. The test results show that the model (fit) can be seen from the values of GFI, AGFI, TLI, CFI, RMSEA and CMIN / DF respectively 0.902, 0.907, 0.964, 0.968, 0.026 and 1.127 which indicate the model fit criteria. The results showed that: 1) Compensation has a significant effect on Quality of Work Life, 2) Compensation has a significant effect on Performance, 3) Quality of Work Life has a significant effect on Performance, 4) Compensation has no significant effect on Performance through Quality of Work Life for Office employees Region of the Directorate General of Customs and Excise, East Java I